Faktor Penentu Minat Beli Produk Makanan dan Minuman Impor Berlabel Halal - Gilang Pandega Mulasakti; Fuad Mas’ud (Jurnal Ilmiah Ekonomi Islam, 2020)
As a country, Indonesia is inseparable from import activities to meet their own needs. Indonesia is a country with the largest Muslim population in the world. Muslims are required to always consume halal food in accordance with Islamic religious orders. However, in fact, not all imported food or beverage products are labeled as halal food. This study aims to analyze the effect of product quality, attitudes, subjective norms, perceived behavioral control and religiosity on the buying interest of Universitas Diponegoro students on imported halal labeled food and beverages.The data collection method is done through questionnaire. The population of this research is Muslim students at Universitas Diponegoro who consume imported food and beverages with sample of 110 respondents. This study uses multiple linear regression analysis techniques that are calculated using the SPSS 26.0 application. The results of the analysis showed that the product quality, attitude, perceived behavioral control and religiosity had a positive and significant effect on the buying interest of Universitas Diponegoro students on imported food and beverage labeled as halal. However, subjective norm are not significant to the buying interest of Universitas Diponegoro students on imported food and beverages labeled halal.